Impacts of Land-Use Change on Runoff Oyo Downstream Sub-Watershed, Bantul Regency, Special Region of Yogyakarta - Anggi Hermawan; Oggi Heicqal Ardian (G-Tech: Jurnal Teknologi Terapan, 2025)
Land use changes from year to year have a significant impact on several flood disasters in the Oyo Downstream River. The purpose of this study was to calculate the amount of surface runoff in the Oyo Downstream Sub-watershed. Runoff discharge can be approximated using an empirical equation, namely by using the rational method. The amount of Runoff in the Oyo Downstream Sub-watershed is determined based on rainfall data for the last 10 years, topographic conditions and land cover conditions in the Sub-watershed area. Based on Google satellite aerial photo images in 2007, 2010, and 2022, changes in land use in the Oyo Downstream Sub-watershed can be seen. The land cover type classification process uses the supervised periodic satellite imagery method, where the results of the classification of each type of land use can be seen in the percentage of land use changes. Based on the results of satellite image analysis, there has been a significant reduction in the area of ​​land cover in forests and trees, namely 28.4% from 2007 to 2023. In contrast to settlements and open land which experienced an increase of 40% and 60% respectively. The results of the calculation of direct runoff discharge in each land cover condition show that there was an increase of 11% from 2007 to 2010, and an increase of 15% from 2010 to 2022. This condition causes flooding in several locations in the Oyo Downstream Sub-Watershed area due to overflowing rivers during the rainy season. In addition, several locations also experience inundation due to poor drainage systems causing rainwater runoff to not be able to flow into the water body/river area.